Invisible Battlefields: Analyzing the Viasat Attack and its Broader Implications - Kazi Arsheen; Kazi Samreen; Bhosale Saloni (Scientific Bulletin, 2025)
The Viasat KA-SAT cyber-attack on February 24, 2022, is an important part of modern cyber warfare. This is a case study that demonstrates how vulnerabilities present in satellite communications can be strategically exploited and result in some severe geopolitical repercussions. This paper also entails the attack's execution, and how the AcidRain malware was deployed, resulting in widespread disruption of internet access in Ukraine and several parts of Europe. The impact was devastating not only affecting core military operations but also critical infrastructures such as the energy systems. The attack is also key in identifying the role of cyber operations in hybrid warfare, where cyber-attacks are integrated into traditional military strategies. Further investigation of the attack has an attribution to Russian state-sponsored attackers, highlighting the challenges of cyber attribution and the international response to a state-sponsored cyber-attack. The paper also delves into the broader implications of the attack, including the necessity for enhanced cybersecurity measures, the recognition of space assets as critical infrastructure, and the need for greater collaboration between governments and security companies to mitigate and manage any future threats.